Microwave-assisted methyl esters synthesis of Kapok (Ceiba pentandra) seed oil: Parametric and optimization study - Bokhari, A. (Green Wave Publishing of Canada, 2015)
The depleting fossil fuel reserves and increasing environmental concerns have continued to stimulate research into biodiesel as a green fuel alternative produced from renewable resources. In this study, Kapok (Ceiba pentandra) oil methyl ester was produced by using microwave-assisted technique. The optimum operating conditions for the microwave-assisted transesterification of Kapok seed oil including temperature, catalyst loading, methanol to oil molar ratio, and irradiation time were investigated by using Response Surface Methodology (RSM) based on Central Composite Design (CCD). A maximum conversion of 98.9 was obtained under optimum conditions of 57.09 Â°C reaction temperature, 2.15 wt catalyst (KOH) loading, oil to methanol molar ratio of 1:9.85, and reaction time of 3.29 min. Fourier Transform Infra-Red (FT-IR) spectroscopy was performed to verify the conversion of the fatty acid into methyl esters. The properties of Kapok oil methyl ester produced under the optimum conditions were characterized and found in agreement with the international ASTM D 6751 and EN 14214 standards. Â© 2015 BRTeam.